Portraying Coronavirus through Metaphors in Online Mass Media Headlines - Raden Indrajid Lukman Sarjono; Barli Bram (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2021)
Online mass media apply metaphors in their headlines to influence the public’s minds regarding a particular issue. Drawing on Lakoff and Johnson’s (1980) Conceptual Metaphorical Theory on understanding, this paper aimed to explore the Coronavirus through metaphors in three notable online mass media headlines in Indonesia and internationally. A qualitative approach was used to analyze the data. The data, consisting of 30 headlines concerning Coronavirus, were collected from headlines of three online mass media and then classified and mapped based on the Conceptual Metaphorical Theory. The process of data analysis was adapted from Metaphor Identification Procedure (MIP) to gain in-depth insights into the use of metaphorical expressions in mass online media. The findings showed that 10 types of metaphors were used in 30 headlines. The two most frequent conceptual metaphors of Coronavirus were Coronavirus as War and Coronavirus as Enemy. Accordingly, online mass media intended to strongly describe the danger of Coronavirus through metaphorical headlines. It may undoubtedly raise people’s fear and anxiety of Coronavirus. Nevertheless, metaphors in online mass media headlines could further function as a preventive rhetorical tool to educate people about Coronavirus as well as equip them with the knowledge to protect from the virus. In conclusion, the metaphors in international and Indonesian online mass media headlines were able to either provide a negative or positive viewpoint toward Coronavirus.